Perspectives on Mental Wellness in Child and Youth Care Education - McDonald, Louise; Pawlick, Nicole; Bellefeuille, Gerard (Advances in Social Sciences Research Journal, 2019)
This course-based research project is conducted in a qualitative interpretive paradigm. The purpose of the inquiry is to gain insight into how students interpret their own subjective experiences and understanding of the impact that the undergraduate child and youth care program at MacEwan University has had on their mental wellness. A purposive sample of four child and youth care students was selected. Data was collected through the use of a semi-structured focus group and a reflective arts-based activity. The data was analysed using Braun and Clarke’s approach to thematic analysis which resulted in the identification of six themes. These include: a) safe and supportive learning environment, b) enhanced understanding, c) genuine student-professor relationship, d) seeing mental health as a strength, e) the healing power of creativity and play, and f) transformational nature of child and youth care education.